Dampak Adanya E – Commerce Terhadap Penurunan Harga di Pasar Tradisional Pada Pasar Tanjung Kecamatan Kaliwates Kabupaten Jember - Manie Sari Ama Putri; Puteri Adiba Wan Noer Azizah; Dhea Amallia (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
With the development of increasingly advanced and developing technology, there are currently many online buying and selling sites where many online sellers are combined into one site which can make it easier for consumers to buy the goods they want with the many attractive promotions or services they provide. to consumers. From an economic perspective, as trade in traditional markets and modern markets increases, this can create job opportunities for many people. More people choose to shop at modern markets because they are more efficient. The existence of e-commerce has become a threat to traditional market sellers, one of which is a decrease in interest and fewer visitors to buy their products. In this analysis we use the theory of social change. In this theory of social change there are several theories, one of which we take is the conflict theory discovered by Karl Marx. With the role of conflict, it creates social change and order in society. In this modern era, technology is increasingly advanced and can make all work or transaction activities easier. Many people have experienced a shift in shopping places, those who initially shopped at traditional markets are now moving to modern markets.